Antisemitism in Medicine: An International Perspective - Michael Gordon; Jerome Teitel; Ted Rosenberg; Ruth Oratz; Naomi Katz; David Katz (Rambam Maimonides Medical Journal)
Throughout history, Jewish people have long been recognized for their achievements in the world of medical science. For example, prior to the Holocaust, many outstanding physicians in Germany were Jewish. However, even in the 1930s, refugee European Jewish doctors faced significant barriers when they tried to escape and practice elsewhere because of long-standing prejudices and anti-Jewish quotas in medical schools and hospitals around the world. Eventually quotas fell, and the period after World War II once again saw a tremendous growth in numbers of Jews excelling in medicine internationally. Since the Hamas attack on Israel on October 7, 2023, there has been a resurgence of antisemitism worldwide. It is especially noticeable in the world of healthcare. This article evaluates and highlights examples of antisemitism in four countries by authors from each of these jurisdictions.